Poplar based agroforestry system: A case study on farmer's field in Haryana - Mandal, B.S.; Mandal, N.; Kaushik, J.C.; Mandal, D.P.S.; Mittal, Varun; ., Ajit (Indian Journal of Agroforestry, 2020)
A case study was conducted to ascertain the performance of different intercrop with poplar at farmer's field of village Haripur in Panchkula district of Haryana adopting poplar based agroforestry system. Poplar (clone G 48) were planted during the year 2004-05 at the spacing of 5 Ã— 2.5 m and harvested during 2009-10. The farmer earned a sum of Rs. 8,70,350 (Rs. 7,89,500 from poplar and Rs. 80,850 from field crops) from one acre in five year rotation, whereas, the income accrued from mono cropping system amounted to Rs. 1,36,990 from one acre. The soil health as well as the protein content in the wheat grain was found better under agroforestry system as compared to mono cropping system. The total leaf biomass added to the soil, through the tree component was to the tune of 1-5.8 quintal per acre.